Pengaruh Motivasi dan Stres Kerja terhadap Kinerja Karyawan pada Bank Nagari Cabang Syari’ah Payakumbuh - Rahmawaty, Dian (Jurusan PIPS FKIP UMMY Solok, 2018)
This study aims to determine the effect of motivation and work stres on the performance of employees of Bank Nagari Branch of Payakumbuh Syari'ah. In connection with the research objectives above, it is hypothesized that